Sex, knowledge, and receptions of the past - Fisher, Kate; Fisher, Kate; Langlands, Rebecca; Langlands, Rebecca (Classical presences, 2015)
The essays in this volume constitute a series of case studies exploring the ways in which claims about the past have been crucial in articulating sexual morals, in driving political, legal, and social change, in shaping individual identities, and in constructing and grounding knowledge about sex. Read together, the chapters invite a consideration of the significance and purpose of writing and thinking about sex in the past; an interrogation of the evidential basis that informs sexual knowledge; and an exploration of the authority used to support such knowledge